2002
DOI: 10.1046/j.1439-0450.2002.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Efficacy of Terbinafine Hydrochloride (Lamisil®) During Oral Treatment of Cats, Experimentally Infected with Microsporum canis

Abstract: Cats represent a primary source of Microsporum canis infections in humans. Terbinafine hydrochloride (Lamisil) is commonly used in the treatment of microsporosis in humans as its fungicidal action permits short periods of treatment. The aim of the present study was to estimate the efficacy of the drug in cats. Nine cats were experimentally infected with M. canis and treated with terbinafine hydrochloride at a dose of 10-20 mg/kg (once daily, SID; low-dose group, LDG). Another nine cats were similarly infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…This study was designed to detect terbinafine concentrations in the hair of cats because dermatophyte infections in animals primarily affect the hair shaft 3 . Although terbinafine is not registered for use in veterinary medicine, it has been successfully used for the treatment of M. canis in several studies 9–13 . The majority of the studies referred here used experimentally infected cats to establish efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was designed to detect terbinafine concentrations in the hair of cats because dermatophyte infections in animals primarily affect the hair shaft 3 . Although terbinafine is not registered for use in veterinary medicine, it has been successfully used for the treatment of M. canis in several studies 9–13 . The majority of the studies referred here used experimentally infected cats to establish efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…High efficacy rates and short treatment times in humans are most likely due to the build up of terbinafine at sites of action. Numerous studies have also shown the successful use of this drug in cats with M. canis infections 9–13 …”
Section: Introductionmentioning
confidence: 99%
“…Although it has been documented that the disease is self‐limiting and healthy animals will eventually self‐cure, treatment is recommended for the following reasons: to speed resolution of the infection, to limit the spread of the infection to other susceptible animals and people, and to minimize contamination of the environment 1–4 . There are many successful treatment protocols in the literature involving daily or pulse therapy administration of a systemic antifungal agent accompanied by appropriate laboratory monitoring of complete blood counts and/or chemistry panels, weekly or twice weekly application of topical antifungal solutions, clipping of the hair coat, confinement, and home hygiene recommendations 5–20 . The published protocols involved pet cats, cattery cats, or cats with experimental infections 3,4,6–14 .…”
mentioning
confidence: 99%
“…The published protocols involved pet cats, cattery cats, or cats with experimental infections 3,4,6–14 . Current treatment recommendations stem from both in vivo and in vitro studies 3,4,6–16,19,20 …”
mentioning
confidence: 99%
“…After a number of studies in animals, scientists have proved that orally administered terbinafine is effective in the treatment of cats suffering from experimentally induced or naturally occurring dermatophytosis (Castanon-Olivares et al 2001, Kotnik 2002, Kotnik and Cerne 2006, Foust et al 2007). Recently topically applied terbinafine showed superior effectiveness in the treatment of experimental M. canis infection in guinea pigs (Ivaskiene et al 2011).…”
Section: Discussionmentioning
confidence: 99%